A novel tacholess order analysis method for bearings operating under time-varying speed conditions. (December 2021) - Choudhury, Madhurjya Dev; Hong, Liu; Dhupia, Jaspreet Singh
Highlights: A tacholess order tracking method for bearing signals is presented. Bearing envelope signal is transformed using Fast Dynamic Time Warping. Smeared fault signatures are squeezed to their individual spectral peaks. Verified by simulation and experiments from laboratory and industrial setup. Abstract: Order tracking (OT) of vibration envelope signal based on instantaneous frequency (IF) estimated from a time-frequency representation (TFR) is generally applied to detect bearing defects under time-varying speed conditions. However, these TFR based OT approaches require a high resolution for accurate estimation of the IF. To overcome these issues, a tacholess OT technique based on the fast dynamic time warping (FDTW) algorithm is applied to detect bearing defects for the first time in this paper. FDTW based signal transformation is initially applied to align a filtered shaft signal to a reference signal of constant frequency, followed by reconstructing the bearing envelope signal. The resulting envelope signal is able to provide a richer fault indication than the original signal. The efficacy of the developed OT method is established using a simulation analysis followed by experimental validation using measurements obtained from a laboratory test-rig and a wind turbine bearing.